Analytical and experimental determination of the failure-critical pressure of pipe structures manufactured by PBF-LB/M - Koers, Thorsten; Magyar, Balázs; Bödger, Christian; Tröster, Thomas (International Journal of Pressure Vessels and Piping)
The state of the art shows that PBF-LB/M offers great potential for pressure-loaded parts, with significant weight reductions and simultaneous optimization of flow resistance. This study is aimed at applying existing calculation methods for pressure-loaded parts to additively manufactured pipe structures, considering the two materials EN AC-43000 (3.2381, AlSi10Mg) and AISI 316L (1.4404, X2CrNiMo17-12-2). For this purpose, systematic tensile tests are carried out for both materials. In addition, a statistical evaluation is performed to determine the design-relevant strength characteristics with a survival probability Ps of 97.5 % for both materials in the as-built and heat-treated condition. Pipe specimens are manufactured, half of which are heat treated, geometrically measured and then subjected to a burst pressure test to experimentally determine the failure-critical internal pressure. These results are compared with calculated burst pressures. The calculations are based on the application-relevant methods identified in this study, considering the strength values determined for the respective material condition. This comparison is used to assess the suitability of the calculation methods for additively manufactured pipe structures, based on the materials investigated.
Keywords: PBF-LB/M; Pipe structures; Strength assessment; Burst pressure test; Geometrical deviations

Phase identification in twin-roll cast Al-Li alloys - BAJTOŠOVÁ, Lucia; Grydin, Olexandr; STOLBCHENKO, Mykhailo; Schaper, Mirko; KŘIVSKÁ, Barbora; KRÁLÍK, Rostislav; ŠLAPÁKOVÁ, Michaela; CIESLAR, Miroslav (METAL 2022 Conference Proeedings)
Al-Li-based alloys are an attractive material for aircraft and aerospace applications. Preparation of these alloys by twin-roll casting (TRC), which combines rapid metal solidification and subsequent plastic reduction in a single processing step, could improve the properties of the alloys compared to materials prepared by conventional direct-chill casting. A commonly used approach for identifying primary phases is a chemical analysis by energy dispersive spectroscopy (EDS). More accurate results can be achieved by combining the method with diffraction analysis. This process can be considerably simplified in microscopes equipped with automated crystal orientation and phase mapping (ACOM-TEM). Al-Cu-Li-Mg-Zr alloy was prepared by twin-roll casting. A combination of TEM and STEM images with chemical analysis by EDS and ACOM-TEM was used to obtain complex information about phases of boundary primary particles. The efficiency of the individual methods for the phase identification in TRC Al-Li-based alloys is discussed.
Keywords: Al-Cu-Li-M-Zr-Fe alloy; twin-roll casting; phase identification; ACOM-TEM

Requirements for Processing High-Strength AlZnMgCu Alloys with PBF-LB/M to Achieve Crack-Free and Dense Parts - Heiland, Steffen; Milkereit, Benjamin; Hoyer, Kay-Peter; Zhuravlev, Evgeny; Keßler, Olaf; Schaper, Mirko (Materials)
Processing aluminum alloys employing powder bed fusion of metals (PBF-LB/M) is becoming more attractive for the industry, especially if lightweight applications are needed. Unfortunately, high-strength aluminum alloys such as AA7075 are prone to hot cracking during PBF-LB/M, as well as welding. Both a large solidification range promoted by the alloying elements zinc and copper and a high thermal gradient accompanied with the manufacturing process conditions lead to or favor hot cracking. In the present study, a simple method for modifying the powder surface with titanium carbide nanoparticles (NPs) as a nucleating agent is aimed. The effect on the microstructure with different amounts of the nucleating agent is shown. For the aluminum alloy 7075 with 2.5 ma% titanium carbide nanoparticles, manufactured via PBF-LB/M, crack-free samples with a refined microstructure having no discernible melt pool boundaries and columnar grains are observed. After using a two-step ageing heat treatment, ultimate tensile strengths up to 465 MPa and an 8.9% elongation at break are achieved. Furthermore, it is demonstrated that not all nanoparticles used remain in the melt pool during PBF-LB/M.
Keywords: grain refinement; crack reduction; laser beam melting; aluminum alloy; titanium carbide; nanoparticle; PBF-LB/M

Mikrostrukturausprägung additiv gefertigter Gitterstrukturen - Sieger, Alexander
Mit Hilfe der additiven Fertigung, insbesondere dem pulverbettbasierten selektiven Laserstrahl-schmelzen (LBM), können hochkomplexe Strukturen endkonturnah hergestellt werden. Die große Designfreiheit ermöglicht, zelluläre Leichtbaustrukturen zu erzeugen, deren mikrostrukturellen und mechanischen Eigenschaften direkt vom generativen Fertigungsverfahren abhängen. Insbesondere im Bereich des Leichtbaus bieten zelluläre Strukturen neue Ansätze zur Verminderung des Energieverbrauchs. Um dieses Potential vollständig ausschöpfen zu können, müssen die Effekte, die zum Versagen der Bauteile mit integrierten Gitterstrukturen führen, quantitativ beschrieben und verstanden werden. Dies ist Voraussetzung für eine sichere Auslegung. Dazu werden im Rahmen der vorliegenden Arbeit die charakteristischen Eigenschaften dieser Strukturen sowie die Einflussgrößen im Aufbauprozess näher beleuchtet. Im Rahmen dieser Dissertation werden numerische und experimentelle Untersuchungen von zwei unterschiedlichen Gitterstrukturtypen aus den Werkstoffen 316L und TiAl6V4 vorgestellt. Beide Werkstoffe werden unter monotoner, einachsiger Belastung getestet. Die parallel dazu durchgeführte digitale Bildkorrelation (DIC) ermöglicht gleichzeitig die detaillierte Analyse der lokalen Dehnungsverteilung während der Verformung. Mikrostrukturelle Eigenschaften und die resultierenden Gittercharakteristika werden mit Hilfe von rasterelektronenmikroskopischen Analysemethoden untersucht. Zudem erfolgt die Entwicklung eines Finite-Elemente- Modells, mit der Anforderung eines möglichst geringen Rechenaufwandes. Ein abschließender Vergleich der realen Dehnungsverteilung mit der FE- Analyse verifiziert das Modell.
Keywords: Additive Fertigung; TiAl6V4; 316L; Gitterstrukturen; L-PBF

Erfolgsfaktoren bei Mergers and Acquisitions – Warum schaffen Portfoliomaster mehr Value Added? - Sievers, Sönke; Mehring, Oliver; Keienburg, Georg; Kengelbach, Jens (Corporate Finance (VHB-JOURQUAL 4 Ranking C))
Unternehmen, die regelmäßig ihr Geschäftsfeldportfolio durch aktives M&A-Geschäft in Form von Verkäufen und Käufen steuern, erzielen deutlich bessere Ein- und Zweijahresrenditen für Aktionäre als alternative M&A-Strategien. Ursächlich hierfür ist u.a., dass die bekannten Effekte in Form von Abschlägen für z.B. diversifizierende Transaktionen oder Stock-Deals deutlich geringer ausfallen als bei Vergleichsgruppen wie z.B. One-Time-Deal Unternehmen. Dieser Beitrag analysiert die Gründe für den Erfolg von Portfoliomastern, Unternehmen die mehr als vier Deals in fünf Jahren durchführen. Durch ein professionalisiertes M&A-Management grenzen sie sich positiv in ihrer mittel- und langfristigen Renditeentwicklung gegenüber Strategic-Shiftern (zwei bis vier Deals) und One-Timern ab. Ihr Erfolg beruht darauf sowohl bei diversifizierenden als auch Stock-Deals bekannte übliche Performanceabschläge zu vermeiden und auch in volatilen Markphasen wertschaffende Deals umzusetzen.
Keywords: M&A; Erfolgsfaktoren; Transaktionsanzahl; Diversifizierung; Volatilität; Cash-Deals; Stock-Deals; Portfoliomaster